2013
DOI: 10.1103/physreve.87.063104
|View full text |Cite
|
Sign up to set email alerts
|

Wave packet spreading and localization in electron-nuclear scattering

Abstract: Despite its promise as a method for the simulation of time-dependent many-body quantum mechanics problems, wave packet molecular dynamics (WPMD) is limited in its use by wave packet spreading when applied to dense plasma systems. We employ more accurate methods to determine if spreading really occurs and how WPMD can be improved. A scattering process involving a single dynamic electron interacting with a periodic array of statically screened protons is used as a model problem for the comparison. We compare the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 49 publications
2
39
0
Order By: Relevance
“…Several studies have suggested that these two contributions are not completely independent, but rather approximately proportional to each other, and that the overall description of the correlation might be improved by a proper scaling of the two terms [58,60,105]. In fact, as shown in Figure 1, the SS and OS potential and DRD, show a very high degree of proportionality, and a proper scaling of the SS potential can reproduce the OS potential [58]. However, so far, this proportionality has been been investigated only in a qualitative manner, we now perform a more quantitative analysis.…”
Section: B Two-dimensional Scan Of the Cos And Css Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have suggested that these two contributions are not completely independent, but rather approximately proportional to each other, and that the overall description of the correlation might be improved by a proper scaling of the two terms [58,60,105]. In fact, as shown in Figure 1, the SS and OS potential and DRD, show a very high degree of proportionality, and a proper scaling of the SS potential can reproduce the OS potential [58]. However, so far, this proportionality has been been investigated only in a qualitative manner, we now perform a more quantitative analysis.…”
Section: B Two-dimensional Scan Of the Cos And Css Parametersmentioning
confidence: 99%
“…One of these is based on a modified MBPT(2) functional with a semi-canonical transformation of the Hamiltonian (OEP2-sc) [14,15,57]. As an alternative, recently a new method (OEP2-SOS) [58] has been proposed in this context, based on the spin-resolved second-order correlation energy expression [59], and especially on the scaled-oppositespin (SOS) variant thereof. This method takes advantage of the improved accuracy demonstrated for spincomponent-scaled (SCS) and SOS second-order Møller-Plesset (MP2) calculations [59,60] and provides an accurate OEP correlation functional that largely outperforms the OEP-GL2 approach [58].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking the decoherence problem into account, the temperature effect on the spreading of wave packet is an essential feature [16]. The theoretical description of relaxation and decoherence processes in open quantum systems often leads to a non-Markovian dynamics which is determined by pronounced memory effects.…”
Section: Introductionmentioning
confidence: 99%
“…There is a great variety of XC approximations. They are usually classified on the so called Jacob's ladder of DFT [3], which includes several families of functionals: local [4][5][6], semilocal [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26], hybrid [27][28][29][30][31][32][33] and fully nonlocal [34][35][36][37] functionals. Each one these families has its own advantages and limitations in terms of accuracy and computational cost.…”
mentioning
confidence: 99%